Practical eminence and experience-based recommendations for use of TNF-α inhibitors in sarcoidosis - Drent, Marjolein; Cremers, Johanna P; Jansen, Tim L; Baughman, Robert P (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: In severe refractory sarcoidosis cases not responding to conventional immunosuppressive treatment, the third-line tumor necrosis factor-alpha (TNF-α) inhibitors infliximab and adalimumab might be an alternative. However, appropriate studies to guide the clinician are lacking. The aim of this study was to establish practical recommendations for the use of TNF-α inhibitors in the management of refractory sarcoidosis patients. Methods: Based on a literature search and the opinion of sarcoidosis experts worldwide, the recommendations were established. Studies conducted in sarcoidosis were supplemented with data obtained from relevant studies in other inflammatory diseases. A Delphi method of polling, using an online survey addressing 12 clinical questions, was performed amongst 20 of the world’s leading sarcoidologists to investigate consensus in case of inadequate data to determine an objective answer. Results: Of the 256 papers found, 101 were included. Randomized controlled trial studies about the use of TNF-α inhibitors in sarcoidosis are limited. Ninety-five percent (19 of 20) of the sarcoidologists contacted, completed the questionnaire (Europe 68%, North America 32%). Nine recommendations were formulated concerning general aspects of TNF-α inhibitor use; Specific sarcoidosis related items, including indications, starting and maintenance dosage, interval of treatment, treatment duration, and discontinuation regimen of infliximab and adalimumab, were addressed. Conclusion: Based on earlier studies and consensus amongst world’s leading sarcoidologists, practical recommendations for the use of TNF-α inhibitors in sarcoidosis were established. These recommendations, with emphasis on indications, dosage and discontinuation regimens, have been developed to support the clinician in the management of refractory sarcoidosis patients.